Advanced nutrition and dietetics in obesity - Hankey, Catherine (Chichester, West Sussex ; Hoboken, NJ : John Wiley & Sons, 2018)
'This addition to the British Dietetic Association Advanced Nutrition and Dietetics book series is written for clinicians and researchers who work with any aspect of obesity and its comorbid conditions. Featuring contributions from leading researchers and practitioners from around the globe Advanced Nutrition and Dietetics in Obesity offers a uniquely international perspective on what has become a worldwide public health crisis. Chapters cover a full range of new ideas and research on the underlying drivers of obesity in populations including discussions on the genetic and clinical aspects of obesity, along with expert recommendations on how to effectively manage and prevent this chronic and persistent disease. Providing a comprehensive overview of the key literature in this field, Advanced Nutrition and Dietetics in Obesity is an invaluable resource for all those all those whose work should or does embrace any aspect of obesity'--Provided by publisher.
Machine generated contents note: 1.1. Definition, prevalence and historical perspectives of obesity in adults -- 1.2. Definition, prevalence and historical perspectives of obesity in children -- 1.3. Development of overweight and obesity across the life course -- 1.4. Diagnostic criteria and assessment of obesity in adults -- 1.5. Diagnostic criteria and assessment of obesity in children -- 2.1. Obesity in the development of type 2 diabetes -- 2.2. Obesity in the development of cardiovascular disease -- 2.3. Obesity as a risk factor in the development of cancer -- 2.4. Obesity as a risk factor in osteoarthritis and pulmonary disease -- 2.5. Psychology and mental health issues in obesity -- 2.6. Binge eating and obesity -- 3.1. Genetics and epigenetics in the aetiology of obesity -- 3.2. Food intake and appetite in the aetiology of obesity -- 3.3. Physiological control of appetite and food intake -- 3.4. Obesogenic medication in the aetiology of obesity -- 3.5. Gut microbiome in obesity -- 3.6. Physical activity and physical inactivity in the aetiology of obesity -- 3.7. Obesogenic environment and obesogenic behaviours -- 4.1. Macronutrient composition for weight loss in obesity -- 4.2. Meal replacements for weight loss in obesity -- 4.3. Formula diets for weight loss in obesity -- 4.4. Group-based interventions for weight loss in obesity -- 4.5. Commercial weight management organisations for weight loss in obesity -- 4.6. Fad diets and fasting for weight loss in obesity -- 4.7. Pharmacological management of weight loss in obesity -- 4.8. Diet to support pharmacological management of weight loss -- 4.9. Surgical management of weight loss in obesity -- 4.10. Diet to support surgical management of weight loss -- 4.11. Physical activity for weight loss in obesity -- 4.12. Psychological interventions for weight loss in obesity -- 4.13. Weight loss interventions in specific groups: overweight and obese men -- 4.14. Weight loss interventions in specific groups: Adults with intellectual disabilities and obesity -- 4.15. Weight maintenance following weight loss in obesity -- 4.16. Economic cost of obesity and the cost-effectiveness of weight management -- 5.1. Genetics, epigenetics and obesity: focus on studies in children -- 5.2. Food intake, eating behaviour and obesity in children -- 5.3. Physical activity and inactivity in the aetiology of obesity in children -- 6.1. Diet in the management of weight loss in childhood obesity -- 6.2. Physical activity in the management of weight loss in childhood obesity -- 6.3. Psychological and behavioural interventions in childhood obesity -- 6.4. Residential programmes and weight loss camps in childhood obesity -- 6.5. Pharmacological management of weight loss in childhood obesity -- 6.6. Surgical management of weight loss in childhood obesity -- 7.1. National campaigns to modify eating behaviour in the prevention of obesity -- 7.2. Increasing physical activity to prevent childhood obesity -- 7.3. Designing public health initiatives for the prevention of obesity.
Includes bibliographical references and index.
Online resource; title from digital title page (viewed on January 31, 2018).
Keywords: Obesity; Reducing diets; Obesity; Diet Therapy; POLITICAL SCIENCE -- Public Policy -- Social Security; POLITICAL SCIENCE -- Public Policy -- Social Services & Welfare; Obesity; Reducing diets; Electronic books